Quaternary high-resolution seismic sequence based on instantaneous phase of single-channel seismic data in the South Yellow Sea, China. (27th February 2018) - Zhao, Weina; Zhang, Xunhua; Wang, Zhongbo; Chen, Shanshan; Wu, Zhiqiang; Mi, Beibei
Abstracts: The South Yellow Sea (SYS) is a semi-closed epicontinental sea with a dense network of seismic reflection profiles, preserving favorable depositional strata. Single-channel seismic has been one of the primary technical methods used to study the characteristics of regional strata sediment since the Neogene period. Based on two cores (CSDP-1 and Qc2) and single-channel seismic data obtained from continental shelf of the SYS in 2013, we present analysis on sequence stratum and evolution environment for the Quaternary around cores CSDP-1 and Qc2 in the Middle and Western sea areas of South Yellow Sea. Identification of instantaneous phase demonstrates more plentiful strata information. Instantaneous phase of marine deposits is seen to continue with horizontal level in most parts, except the areas with some clay and clay silts. Continental units feature poor layering in instantaneous phase profile. Along with the two cores, the result suggests that marine sedimentary time for the core CSDP-1 was longer than that for the core Qc2 since 700 ka, and it may mean the existence of four regressions. Paleo-shoreline lay between cores CSDP-1 and Qc2 during 700–460 ka, 289–270 ka, 75–29 ka, and 13.1–10.3 ka. Different subsidence and climate comprehensively drove the evolution of sedimentation during the Quaternary in SYS.